Tadrīs Mahārah al-Kalām ma’a al-Nāṭiq al-Aṣlī (Mazāyāhu wa Naqāiṣuhu) - Darman, Isra Hayati; Hakim, Rani Ismil (Journal of Language Intelligence and Culture, 2020)
Learning the speaking skill needs practice and a correct example from the teacher. Then, the Islamic Higher Institute Dar al-Qur’an Payakumbuh using the native speaker to teach the speaking skill at that institute. This research aims to find out the implementation of the process of learning the speaking skill with a native speaker, its advantages and disadvantages. The research method used in this research is the descriptive method with qualitative approach analysis. The results of this research are: The first: The process of teaching and learning the speaking skill with the native speaker at the Islamic Higher Institute Dar Al-Qur’an Payakumbuh is implemented to the beginner level. The second: The advantages of learning the speaking skill with the native speaker, including: The students found the example of correct pronunciation from vocabulary and speaking with correct accent, intonation,vocabulary, phrases and styles of the famous Arabic language and used by Arabs. Also, by learning the speaking skill with native speaker, the students found exciting, enthusiastic, and encouraged to upgrade their ability to speak, and the third: disadvantages of learning the speaking skill with the native speaker, which is especially for beginners in the Arabic language, they are difficult to understand the explanation from the teacher because of his speed in speaking, and lack of their Arabic vocabularies, and lack of their comprehension in grammar and morphology.